Django crash course with examples. (Packt Publishing, 2022)
A comprehensive course for those who know Python basics and want to be able to build web apps using Python About This Video Learn the different components of the Django web framework using real-world examples Learn and test for yourself and understand how every component behaves by running them on your browser Understand and apply the communication between Django and the SQL database In Detail The course teaching approach is learn-by-doing. You will learn to build two different apps: a modern Bootstrap blog website with a complete blog author interface and a dynamic Google Translate-like translator web app. The two apps have been chosen carefully to cover all core Django features. The apps are also extendible, allowing you to improve and add features to the apps while sharpening your Django skills and building your own GitHub portfolio. Among other topics, you will learn the model-view-template app structure of Django. You will also learn to set up SQL databases and connect the database with your app. You will learn to build complete web pages equipped with HTML widgets and create HTML forms that handle GET and POST HTTP requests. In addition, you will learn how to create and manage URL patterns for your app pages. You will also learn how to build an admin interface, which is useful when building content websites such as blogs, where content creators and other admins can use the admin interface to add content to the website without interfering with the codebase. You will also get an introduction to HTML and learn to create front-end widgets such as input boxes, buttons, and HTML forms. You will learn to give your web app a modern look by adding Bootstrap styling to your website. By the end of the course, you will have all the skills to build your own web apps using Django, and you will know where to look whenever you need to add new Django features to your apps. Audience The course is beneficial for those who want to turn their ideas into web apps. You will be able to create your own web apps in no time. You will also be able to start your web development career with this course. Finally, the program assumes you know Python basics already. If you know Python basics, you can understand and use the Django codebase to build web applications, and this course will take you step-by-step through that process.